Editorial Team - Editorial Team, (The Toro Historical Review, 2022)
The Toro Historical Review Volume 13, Issue 1 Editorial and Production Team: Daniella Enriquez Jason Kooken Caitlin McClister Christian Palomares Dr. Joshua J. Jeffers, faculty mentor